2022
DOI: 10.1186/s12879-022-07441-z
|View full text |Cite
|
Sign up to set email alerts
|

The impact of public health interventions on the future prevalence of ESBL-producing Klebsiella pneumoniae: a population based mathematical modelling study

Abstract: Background Future prevalence of colonization with extended-spectrum betalactamase (ESBL-) producing K. pneumoniae in humans and the potential of public health interventions against the spread of these resistant bacteria remain uncertain. Methods Based on antimicrobial consumption and susceptibility data recorded during > 13 years in a Swiss region, we developed a mathematical model to assess the comparative effect of different interventions on t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Three models combining nosocomial and community transmission were used to compare the impact of interventions across these two settings. 22,24,27 MacFadden et al fitted a transmission model to observed proportions of ESBL production among E. coli over time in Sweden. 22 They predicted that a 20% decrease in antibiotic use in the community led to greater reductions in ESBL prevalence in both settings (community and hospital) than a same 20% decrease in hospital antibiotic use.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three models combining nosocomial and community transmission were used to compare the impact of interventions across these two settings. 22,24,27 MacFadden et al fitted a transmission model to observed proportions of ESBL production among E. coli over time in Sweden. 22 They predicted that a 20% decrease in antibiotic use in the community led to greater reductions in ESBL prevalence in both settings (community and hospital) than a same 20% decrease in hospital antibiotic use.…”
Section: Resultsmentioning
confidence: 99%
“…The other main type of data considered was aggregated counts of infections sensitive or resistant to a particular antibiotic, by unit of time at the region or country level. These data predominantly came from national surveillance systems, such as in Sweden or Switzerland, 22,27 or at the European level. 24,26 One study used aggregated infection cases from an intervention study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies (7%) with community transmission included zoonotic or foodborne transmission. 29,30 In terms of incorporating movement, we found that two studies (7%) utilized data to investigate the impacts of movement on colonization in the community setting between high and low-prevalence geographical regions 24,31 . Nine studies (31%) incorporated transfers between STACHs; among those studies, three of them modeled additional movement between STACHs and communities.…”
Section: Movement and Transmission Characteristicsmentioning
confidence: 99%